polynomials am i doing it right?
posted by anonymous .
1) (x^4+7x^3+7)(2x^44x^3+1)
= x^4+3x^3+6
2) (3n^3+n^2n4)+(5n^34n^2+11)
= 8n^33n^2n+11

You're on the right track...
1. expand it and write it out when it is a subtraction:
(x^4+7x^3+7)(2x^44x^3+1)
= x^4+7x^3+7) 2x^4+4x^31
= x^4 + 11 x^3 + 6
2. space out your terms to avoid losing some of them.
(3n^3 + n^2 n 4)+(5n^3 4n^2 + 11)
= 3n^3 + n^2 n 4 + 5n^3 4n^2 + 11
= 8n^3  3n^2 n + 7 
for #1 i did
(x^4+7x^3+7)(2x^44x^3+1)
= x^4+7x^3+72x^44x^31
= x^4+3x^3+6
so why is it wrong? 
because you see that when you expanded the polynomials after the 2x^4 yu have a  instead of a positive because recall that when the brackets expand  and  = +.
That is the only thing you did wrong.
Good luck! you are on the right track though. 
ok thank you

no problem:)